A prospective study of the performance of resin bonded bridgework in patients with hypodontia. (July 2016) - Allen, Patrick Finbarr; Anweigi, Lamyia; Ziada, Hassan
Abstract: Congenital absence of teeth presents a number of clinical challenges in young patients, and little is known about the success rate of restorative dental treatment in these patients. The aim of this study was to conduct a prospective clinical study of the performance of resin bonded bridges in patients with hypodontia. Methods: A prospective clinical observation study was undertaken in Cork Dental School and Hospital, Ireland. Forty patients (22 males, 18 females; age range 18–21 years) with a confirmed diagnosis of hypodontia rated as mild (n = 26), moderate (n = 8) or severe (n = 6) participated. Following completion of the orthodontic phase of care, all patients had missing teeth restored with resin bonded bridgework (RBB) using a standardised protocol (48 FF; 17CL design). Patients were followed up for 24 months, with recall visits at 6, 12 and 24 months following provision of RBBs. Results: 65 RBBs were provided, 49 in the maxilla and 16 in the mandible; 43 bridges replaced anterior teeth and 22 replaced posterior teeth. After 24 months, 63 bridges were still in function and deemed to satisfy the preset criteria for success and survival. Two posterior bridges had failed due to repeated debond, and this was attributed to occlusal overload. 20% of the patients demonstrated some evidence of post orthodontic relapse, but this did not require further intervention. Conclusion: In the short to medium term, resin bonded bridgework provides a reliable and minimally invasive solution for replacing missing teeth in patients with hypodontia.